2019
DOI: 10.1038/s41598-019-43209-3
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin-receptor kinase fused gene (TFG) regulates lipid production in human sebocytes

Abstract: The endoplasmic reticulum (ER) is an organelle in which important cellular events such as protein synthesis and lipid production occur. Although many lipid molecules are produced in the ER, the effect of ER-organizing proteins on lipid synthesis in sebocytes has not been completely elucidated. Tropomyosin-receptor kinase fused gene (TFG) is located in ER exit sites and participates in COPII-coated vesicle formation along with many scaffold proteins, such as Sec. 13 and Sec. 16. In this study, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In other cell systems, TFG has been described as a negative regulator of the UPS, and its overexpression can lead to increased ER stress by interfering with ERAD [53]. Additionally, some non-immune secretory cells like insulin-producing β-cells [54] or sebocytes [55] also depend on TFG. While the functions of TFG may vary in different cell types and may depend on its abundance, all published data point to a function of TFG in homeostasis of the ER and the secretory pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In other cell systems, TFG has been described as a negative regulator of the UPS, and its overexpression can lead to increased ER stress by interfering with ERAD [53]. Additionally, some non-immune secretory cells like insulin-producing β-cells [54] or sebocytes [55] also depend on TFG. While the functions of TFG may vary in different cell types and may depend on its abundance, all published data point to a function of TFG in homeostasis of the ER and the secretory pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Using an immortalized human sebocyte cell line that was established previously 7 , we first investigated the effect of azidothymidine on IGF-1-induced lipogenesis. The immortalized human sebocytes were treated with 10 or 25 µ M of azidothymidine.…”
Section: Resultsmentioning
confidence: 99%
“…Although IGF-1′s role in lipid production in sebocytes is well documented 7 14 , the role of IGF-1 in mitochondrial homeostasis in sebocytes has not been sufficiently investigated. In this study, we investigated the effect of IGF-1 on the mitochondria of sebocytes and found that IGF-1 increased the levels of PGC-1α and mtTFA in the immortalized human sebocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations